Boiotia in Ancient Times : Some Studies of its Topography, History, Cults and Myths - Fossey, John M., (Classical Studies E-Books Online, Collection 2020, ISBN: 9789004393820., 2019)
This is the concluding volume presenting results of the author's fieldwork spread over more than fifty years concerning the Archaeology and Topography of Ancient Boiotia that includes also discussions of the distribution within the topography of certain ancient cults, especially those of Artemis, Herakles and the Horseman Hero. Within the more purely topographic section there is much discussion of regional defense systems, all set against the history of the Boiotian League, especially its early coinage, its origins and its confrontation with Sparta and the pivotal battle of Leuktra.